Treatment of Antibiotic Cephalexin by Heterogeneous Electrochemical Fenton-Based Processes Using Chalcopyrite as Sustainable Catalyst - Salazar-Gonzalez, R (Elsevier B.V., 2020)
The development of heterogeneous Fenton-based electrochemical advanced oxidation processes is important for the removal of organic pollutants at industrial level in the near future. This work reports the application of heterogeneous photoelectro-Fenton (HPEF) with UVA light as an enhanced alternative to the more widespread heterogeneous electro-Fenton (HEF) process. The treatment of the antibiotic cephalexin using chalcopyrite as a sustainable catalyst was studied using an undivided IrO2/air-diffusion cell. XPS analysis showed the presence of Fe(III), Cu(I) and Cu(II) species on the surface. The amount of Fe2+ ions dissolved upon chalcopyrite exposure to continuous stirring and air bubbling was proportional to chalcopyrite content. In all cases, the occurrence of pH self-regulation to an optimum value near 3 was observed. The HEF and HPEF treatments of 100 mL of 50 mg L−1 cephalexin solutions with 0.050 M Na2SO4 have been studied with 1.0 g L−1 chalcopyrite at 50 mA cm−2. Comparative homogeneous EF and PEF with dissolved Fe2+ and Cu2+ catalysts were also performed. HPEF was the most effective process, which can be mainly explained by the larger production of homogeneous and heterogeneous [rad]OH and the photodegradation of the complexes formed between iron and organics. The effect of applied current and catalyst concentration on HPEF performance was assessed. Recycling experiments showed a long-term stability of chalcopyrite. Seven initial aromatics and six cyclic by-products of cephalexin were identified, and a plausible degradation route that also includes five final carboxylic acids is proposed. © 2020 Elsevier B.V.